Knowing Words : Wisdom and Cunning in the Classical Traditions of China and Greece - Raphals, Lisa (Myth and poetics., 2018)
For the Greeks, the craft of Odysseus and the wisdom of Athena were examples of metis, an elusive cast of mind that ranged from wisdom and forethought to craft and cunning. Although it informed many aspects of Greek society, metis was all but absent from the language of Greek philosophy. Invoking Indigenous Chinese debates, Lisa Raphals here examines the role and significance of metic intelligence in classical Chinese philosophy, literature, history, and military strategy. Raphals first examines the range of meanings of the Chinese word zhi. As with the Greek metis, the uses of zhi include "wisdom, " "knowledge, " "intelligence, " "skill, " "cleverness, " and "cunning." Drawing on parallels between the two traditions, she argues that, in China as in Greece, metic intelligence tacitly informed many aspects of cultural and social life. In China, these included views of the nature of knowledge and language, standards of personal and social morality, and theories of military strategy and statecraft. After surveying representative texts from the Warring States period, Raphals considers the function of metic intelligence as the dominant quality of central characters in two novels from the Ming dynasty, the Romance of Three Kingdoms and Journey to the West. Finally, she compares the treatment of themes of heroism and recognition in the Chinese and Greek narrative traditions. Knowing Words will be welcomed by sinologists, classicists, and scholars of comparative philosophy and literature.